Analysis of Beginning Reading Difficulties in Third Grade Students of SDN 1005 Sidomulio, South Barumun District - Ummi Khoiriah Hsb; Tri Indah Kusumawati (South Sulawesi Education Development (SSED), 2024)
Beginning reading is an activity that is carried out in an integrated manner, including recognizing letters and words and then connecting them with their sounds and meanings so as to obtain conclusions about the meaning of the reading. The learning process in early reading is carried out by recognizing language in writing, through writing students are required to be able to pronounce the symbols of language sounds with sounds that produce clear meaning, accuracy and success at the early reading stage will have a major impact on improving further reading skills. The research aims to find out the difficulties of beginning reading for third grade students at SDN 1005 Sidomulio, South Barumun Subdistrict, researchers obtained information that there were several students who had difficulties in beginning reading. This type of research is qualitative research with descriptive methods. The subjects of this research are several students who still have difficulty reading, especially beginning reading, namely 6 students. The data collection techniques used were interview, observation, and documentation techniques. The results obtained from this study are the difficulties experienced by students, including those who do not recognize letters, still have difficulty saying words without spelling, still have difficulty spelling difficult words and do not recognize some letters. Factors that hinder students in beginning reading are psychological factors, environmental factors and lack of interest and motivation and environmental factors where the lack of parental attention in teaching children to read when at home.